Implementation of E-Commerce System as SME Development Strategy in the Digital Era - Maulian Saputra; Susilawati; Siti Nurhaliza Sofyan; Ananda Aulia; Andi Ernawati; Ayu Oftasari; Rian Farta wijaya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The implementation of e-commerce systems has become one of the main strategies in the development of Small and Medium Enterprises (SMEs) in the digital era. E-commerce allows SMEs to expand market reach, improve operational efficiency, and strengthen relationships with consumers through better data access. In addition, this digital platform offers benefits such as distribution cost savings, business process automation, and improved customer service. However, challenges in e-commerce adoption for SMEs include limited digital literacy, uneven technology infrastructure, and cybersecurity issues. To achieve the full potential of e-commerce, support from the government and private sector in the form of adequate policies, infrastructure, and training is required. This research aims to identify the benefits, challenges and solutions in implementing e-commerce for SMEs, in order to improve their competitiveness in an increasingly competitive global market.